A Natural Disaster Reshapes Prosocial Microlending - Ding, Yi; Xu, Haifeng; Tan, Bernard C. Y. (Information Systems Research, 2025)
Research Spotlight A natural disaster may result in a situation where lenders can hardly find appropriate loans from the disaster-affected region. When faced with the mismatch between the supply and demand of microloans, lenders can either simply choose not to make any contributions or divert their prosocial intentions towards a different group of beneficiaries. Using a natural experiment based on the Ebola outbreak in Africa in 2014, our research shows that a natural disaster increases (over the short-term) the average contribution size and decreases (over the long-term) the average fundraising time per dollar for prosocial microloans by borrowers from regions closer to the affected region. In contrast, a natural disaster decreases (over the long-term) the average contribution size and increases (over the long-term) the average fundraising time per dollar for prosocial microloans by borrowers from regions farther away from the affected region. This redistribution of prosocial microlending is an unintended consequence of a natural disaster that inflicts long-term economic hardship in some regions. Policymakers and researchers should closely monitor the redistribution of prosocial microlending resulting from a natural disaster so that prompt action can be taken to alleviate potential negative consequences that may arise.